Autism Occurrence by MMR Vaccine Status Among US Children With Older Siblings With and Without Autism. Issue 8 (August 2015) - Jain, Anjali; Marshall, Jaclyn; Buikema, Ami; Bancroft, Tim; Kelly, Jonathan P.; Newschaffer, Craig J.
<x xml:space="preserve">Abstract</x> ABSTRACT While a large body of research has found that the measles-mumps-rubella (MMR) vaccine is not linked to autism spectrum disorder (ASD), there is still a popular belief that the vaccine causes ASD. This belief, coupled with the fact that the younger siblings are genetically at risk of autism, might cause parents to avoid vaccinating those children. While previous small studies found no significant difference in diagnosis rates between immunized and nonimmunized children with older siblings with ASD, this retrospective cohort study aims to report on ASD occurrence by MMR vaccine status in a larger sample. The Optum Research Database, an administrative claims database associated with a large US health plan, was used to conduct this study. The cohort group included children who were enrolled in the plan for their first 5 years of life or more during 2001 to 2012, who had an older sibling enrolled for at least 6 months. To compare ASD rates between children who were vaccinated or not vaccinated at various ages, relative risks were estimated. The cohort included 95, 727 children. A total of 1929 children in the cohort had an older sibling with ASD diagnosis. Of those, 134 (6.9%) were also diagnosed with ASD. Among the children without siblings with ASD, 890 (0.9%) were diagnosed with ASD. The rate of vaccination was higher for children with siblings without ASD (84% [n = 78, 564] at 2 years and 92% [n = 86, 063] at 5 years) than for children with siblings with ASD (n = 1409 [73%] at 2 years and n = 1660 [86%] at 5 years). In children with unaffected older siblings, unadjusted relative risk (RR) of ASD for 1 dose of the vaccination at 2 years of age compared with no dose was 0.80 (95% confidence interval [CI], 0.44–1.47; P = 0.58), and in children with older affected siblings, that RR was 0.44 (95% CI, 0.15–1.29; P = 0.22). No association was found between 1 dose of MMR at ages 3, 4, and 5 years and ASD, whether or not their older siblings had ASD. The unadjusted RR of ASD for 2 doses of MMR at 5 years in children with unaffected older siblings was 0.74 (95% CI, 0.55–0.99; P = 0.049), and in children with siblings with ASD, RR was 0.44 (95% CI, 0.26–0.75; P < 0.01). Adjusted RR for 1 dose at age 2 years in children with older siblings with ASD was 0.76 (95% CI, 0.49–1.18; P = 0.22), and for children who received 2 doses at age 5 and had older siblings with ASD, RR was 0.056 (95% CI, 0.31–1.01; P = 0.052). In children who did not have older siblings with ASD, RR for 1 dose at age 2 years was 0.91 (95% CI, 0.67–1.20; P = 0.50), and for 2 doses at age 5 years, RR was 1.12 (95% CI, 0.78–1.59; P = 0.55). These observations were consistent with previous studies in that no association was found between MMR vaccination and increased risk of ASD in the cohort in privately insured children, and no evidence was found that risk of ASD was associated with 1 or 2 doses of the vaccine in children with older siblings with ASD.